2018
DOI: 10.1111/jgh.14097
|View full text |Cite
|
Sign up to set email alerts
|

Management of achalasia cardia: Expert consensus statements

Abstract: Achalasia cardia (AC) is a frequently encountered motility disorder of the esophagus resulting from an irreversible degeneration of neurons. Treatment modalities are palliative in nature, and there is no curative treatment available for AC as of now. Significant advancements have been made in the management of AC over last decade. The introduction of high resolution manometry and per-oral endoscopic myotomy (POEM) has strengthened the diagnostic and therapeutic armamentarium of AC. High resolution manometry al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 124 publications
(309 reference statements)
0
22
0
1
Order By: Relevance
“…The study published in 2018 by Teitelbaum et al also showed a decrease in the clinical success rate ▶ of POEM in Achalasia patients to around 83 % at 5 years followup. This has been traditionally explained by the degenerative nature of Achalasia and the fact that all available treatments are rather palliative than curative [24]. On the other hand, Hungness et al reported the durability of POEM after following 115 patients for an average of 2.4 years post-POEM, showing a stable clinical success rate of 92 %.…”
Section: Discussionmentioning
confidence: 99%
“…The study published in 2018 by Teitelbaum et al also showed a decrease in the clinical success rate ▶ of POEM in Achalasia patients to around 83 % at 5 years followup. This has been traditionally explained by the degenerative nature of Achalasia and the fact that all available treatments are rather palliative than curative [24]. On the other hand, Hungness et al reported the durability of POEM after following 115 patients for an average of 2.4 years post-POEM, showing a stable clinical success rate of 92 %.…”
Section: Discussionmentioning
confidence: 99%
“…Peroral endoscopic myotomy (POEM): a comparative study between Chagasic and idiopathic achalasia Esophagogastroduodenoscopy (EGD) and the barium esophagogram are auxiliary tests. Endoscopic, pharmacological or surgical options are available for treatment of achalasia [9,10]. Currently, laparoscopic Heller myotomy (LHM) is considered the standard surgical method.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, laparoscopic Heller myotomy (LHM) is considered the standard surgical method. However, in recent years, peroral endoscopic myotomy (POEM) has gained popularity due to its excellent safety and efficacy profile [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…POEM is a suitable procedure for naïve patients, patients with a prior treatment failure as well as for patients with sigmoid-type achalasia (although a skilled endoscopist is required) due to its safety and efficacy. Patients with end-stage achalasia (tortuous or sigmoid esophagus type II, classified based on computed tomography) may require esophagectomy [13].…”
Section: Discussionmentioning
confidence: 99%
“…The questions asked in the medical interview include changes in the amount of meals consumed and changes in body weight after the procedure, compared to before the procedure. Esophageal symptoms such as dysphagia and chest pain were also included in the interview and can be measured by Eckardt scores [13]. The opening of the esophagogastric junction by gastrointestinal endoscopy should also be evaluated and compared with pre-POEM.…”
Section: Discussionmentioning
confidence: 99%